FOSTERING STUDENTS’ CRITICAL THINKING AS A KEY FACTOR FOR READINESS IN SOCIAL INTERACTION AND CIVIC COMPETENCE (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
In today’s rapidly evolving global society, developing critical thinking skills in students has become a fundamental priority of modern education systems. Critical thinking enables students to analyze information, evaluate arguments, and make informed decisions, thereby equipping them with essential skills for active participation in social interactions and civic life. This article examines the role of critical thinking in fostering students’ readiness for effective social engagement and the acquisition of civic competences. The study highlights key pedagogical strategies for nurturing critical thinking within classroom environments, emphasizing the importance of creating an open, interactive, and inquiry-based learning atmosphere. It also identifies current challenges faced in the integration of critical thinking into educational practices and proposes practical solutions to enhance its development among school learners. The findings suggest that embedding critical thinking into everyday learning processes not only improves students’ intellectual capacities but also promotes their social adaptability, emotional intelligence, and responsible citizenship. This makes critical thinking an indispensable component of education aimed at preparing students for life in democratic and socially dynamic communities.